THE LEADERSHIP STYLE OF THE HEAD OF RELIGION MINISTRY IN TOLITOLI REGENCY - Arsyad, Daniati (Katalogis, 2015)
This research aims to understand about the leadership style of the ministry of religion’s leader in Tolitoli regency. The theoretical perspective of Path-goal is used as an analytical guide (Robert J. House, 1960). This is descriptive qualitative inquiry. There are eight informans interviewed. The data collection consists of observation, interview, and documentation. The collected data is analyzed through three steps: data reduction, data explanation, and conclusion. The results gained by the four path-goal theoretical perspectives explain how the leadership styles of the leader of the religion ministry in Tolitoli regency are. By the directive leadership view, leadership is implemented in: instruction for the job that should officers to do; division of labor based on the procedure; and division labor based on the skill. By the supportive leadership view, leadership is implemented in: the support of the leader bases on the good impact to the interest of organization; giving jobs communicatively; and opened in time whether formal or informal time. By the participative leadership view, leadership is implemented in: the officers are involved in jobs by the competence they have; and involving of officers in terms of the making decision process. By the achievement orientation leadership view, leadership is implemented in: appreciation gift based on the job performance; giving certain incentives; sanction for violation; and the opportunities for the officers to upgrade their competency by education and training as well.